Hero-cult in Plato’s Phaedo, Republic and the Laws - Petraki, Zacharoula (2021)
Plato’s Phaedo aims to restore the reputation of Socrates by transforming him from a political scapegoat of Athens to a hero of the city who had put him to death. As scholars have shown, the dialogue’s heroization of Socrates shares affinities with the religious tradition of the hero cult (see White, 2000; Nagy, 2015). In this article I argue that the conceptualization of the philosopher as a cult hero is developed further in the Republic and the Laws. The Republic presents Socrates as the “oikist” of the ideal polis, who makes religious decisions under the authority of god Apollo. In the same vein, the distinguished classes of the philosopher-rulers in the Republic and of the auditors in the Laws are compared to another group also subsumed under the category of cult-heroes, the victorious Olympic athletes.